“LAUGHING MATTERS” INTO EFL: INVESTIGATING THE IMPACT OF HUMOR ON STUDENT ENGAGEMENT AND MOTIVATION - Idris Sadri (UIN Sumatera Utara, 2026)
Humor, a powerful tool in human interaction, has the potential to significantly impact language learning. This study investigates the impact of humor on the engagement and motivation of Indonesian EFL students. By analyzing the use of humor in popular Indonesian podcasts like @itsindahg and @whatisupindonesia, this research aims to uncover the specific strategies employed by the hosts to engage their audience. The study will employ a mixed-methods approach, combining quantitative and qualitative research techniques. Quantitative data will be collected through surveys and questionnaires to measure students' perceptions of humor and its impact on their motivation. Qualitative data will be gathered through focus group discussions and content analysis of the podcasts to identify the specific humor techniques used and their effects on audience engagement. It is anticipated that the findings of this study will provide valuable insights into the role of humor in language learning and offer practical implications for EFL teachers in Indonesia.